Evaluating the Economic Impact of Airborne Infectious Diseases on the Health System: A Cross-sectional Study Utilizing Disability-adjusted Life Years and Lost Productivity - Alireza Ghorbani; Hadi Lotfi; Ali Taj; Zahra Keyvanlo; Mohammad Hosseinzadehhesari; Mohammad Miri (International Journal of Environmental Health Engineering)
Aim: Airborne infectious diseases have many adverse economic effects worldwide. However, evidence of these effects in low- and middle-income countries is still scarce. We, therefore, aimed to evaluate the socioeconomic burden of the COVID-19 pandemic as the most important infectious disease in the recent decade by estimating disability-adjusted life years (DALYs) and lost productivity. Methods: This cross-sectional study was based on 456 patients with COVID-19 diseases in Sabzevar, Iran, 2020–2021. We used Murray and Lopez’s approach to calculate the burden of disease. The data on COVID-19 were collected from the Hospital Information System at Vaseie Hospital. Lost life after premature death (years of life lost [YLL]) and life with a disability (years lived with disability [YLD]) were used to measure DALY. The Human Capital Approach (HCA) was used to estimate Temporary Productivity Loss (TPL). Results: During the study period, 6456 patients with the COVID-19 disease were identified, of which 1028 cases resulted in death. The burden of disease caused by COVID-19 was 18,748 DALYs with a discount rate of 3%. The YLL was 4782 in men and 3597 in women. Moreover, YLD was 5283 and 5086 in males and females, respectively. The total costs of productivity loss due to absenteeism (TPL) and due to COVID-19 premature mortality were about $4 and $8 million purchasing power parity for all working-age classes, respectively. Conclusion: Overall, our study suggested that the main burden of COVID-19 was morbidity. YLD was responsible for about 55% of DALYs and males had a higher YLL and YLD than females.